Analisis Resepsi Konten Pada Akun TikTok @vmuliana Terhadap Kebutuhan Informasi Akan Career Preparation - Uljanatunnisa; Putri, Firly Aldrina (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2023)
The purpose of this research is to examine followers meaning of career information on TikTok accounts using the Stuart Hall reception method. There is an increase in the number of unemployed among the younger generation aged 20-24 years and the low success rate of jobseekers in the selection process is due to their lack of information regarding good career preparation. For this reason, the presence of the @vmuliana TikTok account seeks to provide solutions to all career problems that occur. Researchers focused on the content of the TikTok account @vmuliana regarding career preparation tips needed by students in the playlists "Tips for Making CVs", "Contekan Interviews", and "Help Netizens Get Jobs". Researchers collected data through interviews with research subjects, namely students as followers of @vmuliana, documentation, and literature studies. The research used a purposive sampling technique in which later the results of the interview data will be analyzed through 3 stages of the reception methodology namely the collection, analysis, and interpretation of reception data. The results showed that of the five informants, 2 informants were in dominant positions and 3 were in negotiating positions. The existence of differences in the meaning of informants is influenced by the contextual factors of each informant, such as educational background, life experience, and individual knowledge level.